Tanzania's human papillomavirus (HPV) vaccination program: Community awareness, feasibility, and acceptability of a national HPV vaccination program, 2019. (31st March 2022) - Li, Anyie J.; Manzi, Fatuma; Kyesi, Furaha; Makame, Yusuf; Mwengee, William; Fleming, Monica; Mkopi, Abdallah; Mmbaga, Selemani; Lyimo, Dafrossa; Loharikar, Anagha
Abstract: Background: In April 2018, Tanzania introduced the human papillomavirus (HPV) vaccine nationally to 14-year-old girls, utilizing routine delivery strategies (i.e. vaccinating girls at health facilities and community outreach, including schools). We sought to assess awareness, feasibility, and acceptability of the HPV vaccination program among health workers and community-level stakeholders. Methods: We conducted cross-sectional in-person surveys among health workers, school personnel, community leaders, and council leaders in 18 council areas across six regions of Tanzania in October–November 2019. Regions were purposively selected to provide demographic, geographic, and vaccination coverage variability; sub-regional levels used random or stratified random sampling. Surveys included questions on HPV vaccine training and knowledge, delivery strategy, target population, and vaccine and program acceptability. Descriptive analysis was completed for all variables stratified by respondent groups. Results: Across the 18 councils, there were 461 respondents, including health workers (165), school personnel (135), community leaders (143), and council leaders (18). Over half of each respondent group (50–78%) attended a training or orientation on HPV vaccine. Almost 75% of the health workers and school personnel respondent groups, and less than half (45%) of community leaders correctly identified the target age group for HPV vaccine. Most (80%) of the health workers indicated HPV vaccination was available at health facilities and schools; most (79%) indicated that the majority of girls receive HPV vaccine in school. Approximately half (52%) of all respondents reported hearing misinformation about HPV vaccine, but 97% of all respondents indicated that HPV vaccine was either "very accepted" or "somewhat accepted" in their community. Conclusion: The HPV vaccination program in Tanzania was well accepted by community stakeholders in 18 councils; adequate knowledge of HPV vaccine and the HPV vaccination program was demonstrated by health workers and school personnel. However, continued technical support for integration of HPV vaccination as a routine immunization activity and reinforcement of basic knowledge about HPV vaccine in specific community groups is needed. The Tanzania experience provides an example of how this vaccine can be integrated into routine immunization delivery strategies and can be a useful resource for countries planning to introduce HPV vaccine as well as informing global partners on how to best support to countries in operationalizing their HPV vaccine introduction plans.